Processo de reparo de enxerto ósseo particulado em defeito de calota craniana de coelhos sob influência da laserterapia de baixa potência e inibição de COX-2 - Comparin, Éliston (2016)
Rehabilitate the stomatognathic system is perhaps the major challenge of the current dentistry: recovering form, function and aesthetics. The search for new techniques that facilitate bone reconstruction, reducing financial costs, emotional, and the treatment time are goals that must be achieved. The present study aims to investigate the process of particulate autogenous bone graft in repair skull defects of rabbits using anti-inflammatory drugs non-steroidal specific for COX-2 and low-power laser therapy. Twenty-four male New Zealand type rabbits were divided into two groups: Group 1: Low-power laser therapy (LTB) and group 2: LTB more non-steroidal anti-inflammatory drug (NSAID). Animals of group 1 and group 2 received 4 points of LTB applications (AI-GA-AS 808nm, CW, 30 mW, 0.028 cm2, 15 seconds of irradiation, 16J / cm2 per point, totaling 64j / cm2 per session) animals in group 2 were orally dosed with the drug etoricoxib in the proportion of 6 mg / day K. After periods of 7, 14 and 30 days the animals were sacrificed, and the grafted areas removed for microscopic morphological analysis, histomorphometry and immunohistochemistry for COX-2 and vascular endothelial growth factor (VEGF). The data from histomorphometric analysis were subjected to statistical tests of Kruskal Wallis with individual comparisons undertaken by the Miller test where there was a statistically significant difference between group 1 LTB (median 271.5 points) and group 2 LTB + NSAID (181 5 median points) for 14 days only. In immunohistochemical analysis using COX-2 protein as a marker, we found that the 14-day period, there was a more obvious bone formation in group 1 LTB, indicating that the absence of the NSAID improved bone healing will be shown. We concluded that the group that used only LTB in 14 days got a better response to bone repair when compared to the group using more NSAID LTB